Serum IL-35 Levels Are Associated With Activity and Progression of Sarcoidosis - Mengmeng, Zhao; Jiacui, Song; Shanshan, Du; Yuan, Zhang; Ying, Zhou; Qiuhong, Li; Dong, Weng; Hui-Ping, Li (Frontiers in Immunology, 2020)
Objective: To investigate the relationship of interleukin (IL)-35 with sarcoidosis. Methods: We enrolled 114 inpatients and outpatients with sarcoidosis at the Shanghai Pulmonary Hospital, and 24 healthy controls between March 2015 and December 2017. Serum and whole blood were collected during the follow-up period. Serum IL-35 levels were detected by ELISA. Proportions of Breg, Tfh and Treg cells in the peripheral blood were detected using flow cytometry (FCM). The mRNA levels of p35, EBI3 and GAPDH in CD19+ cells and CD4+ cells were detected by real-time PCR. Sarcoidosis granuloma mice models were established with Propionibacterium acnes (PA) and one group was treated with IL-35 antibodies. Proportions of Breg, Tfh and Treg cells in the peripheral blood and bronchoalveolar lavage fluid (BALF) were detected by FCM. Results: The IL-35 levels and the proportions of Breg and Tfh cells in the peripheral blood of patients with active sarcoidosis were significantly higher compared to patients with stable sarcoidosis and healthy controls. Moreover, the IL-35 level in patients with progressive disease was lower than that found at the initial visit. EBI3 and p35 mRNA levels in CD19+ cells for patients with active sarcoidosis were significantly higher as compared to patients with stable sarcoidosis and healthy controls, while there were no significant differences in p35 and EBI3 mRNA levels in CD4+ cells between the three groups. In the mouse model of sarcoidosis, there were loose granulomata (macrophage accumulation in the bronchial areas and immature granuloma) after intervention with IL-35 antibodies. Meanwhile, the proportions of Breg cells in the peripheral blood and BALF of the model were significantly increased, while the proportion of Treg cells declined significantly. After intervention with IL-35 antibodies, the proportion of Breg cells in the peripheral blood of mice decreased significantly as compared to the mice not exposed to anti-IL-35 antibodies. Conclusion: IL-35 levels increased significantly in the serum of patients with active sarcoidosis, and lower IL-35 levels were correlated with persistent disease. Serum IL-35 levels might be better correlated with Breg cell functions.